Physicochemical and tissue response of PLA nanofiber scaffolds sterilized by different techniques = Evaluación fisicoquímica y respuesta tisular de andamios nanofibrilares de PLA esterilizados por diferentes técnicas - Mendieta Barrañon, Isarai
In recent years, tissue engineering has evolved considerably, due to the problems in the biomedical area concerning tissue regeneration therapies. Currently, work has been focused on the synthesis and physicochemical characterization of poly lactic acid scaffolds, a synthetic polyester that has been extensively study for its excellent biocompatibility and biodegradability. Moreover, sterilization strategies of scaffold are a crucial step for its application in tissue regeneration, however, the sterilization process have to maintain the structural and biochemical properties of the scaffold. Therefore, it is very important to carry out studies on the sterilization methods of the sample's material, since translational medicine is intended for in vivo applications. The aim of the present study was designed to analyze the effects of different sterilization techniques, i.e. ethylene oxide (ETO), gamma radiation (GR) and hydrogen peroxide-based plasma (H2O2) in biodegradable PLA scaffolds, and to determine the best sterilization technique to render a sterile product with minimal degradation and deformation, and good tissue response. Analysis of surface morphology showed that ETO and GR modified the PLA scaffolds without any change in its chemical composition. Moreover, the histological response showed that the scaffolds are biocompatible and those sterilized by GR showed a more severe inflammatory response, accompanied with the presence of giant foreign body cells. In conclusion, the results show that among sterilization techniques used in the preset study, the best results were observed with H2O2 sterilization, since it did not significantly modify the surface structure of the PLA fibers and their in vivo response did not cause an unfavorable tissue reaction.